Performance Evaluation of Routing Protocols for Mobile Ad Hoc Networks Using Statistical Taguchi's Experimental Design - Lee, MH; Sarahintu, M; Mohamed, H; Sanugi, B; Olariu, S; Zaharim, A (World Scientific And Engineering Acad And Soc, 2024)
Indexed by WOS